O princípio da Indução Finita e jogos para o ensino de funções - Martins, Rosilaine Sanches [UNESP] (2015)
The proposal of this work is to relate functions, progressions, principle of mathematical induction and games for the learning of mathematics. Applied games are Torre de Hanói, Jogos dos Anéis Chineses and Salto de Rã game, as well as an activity with cubes. The use of games in this work is not intended at the construction of concepts, but the use of definitions learned in the classroom in the activity of entertainment. Thus, forms have been prepared which led students to an investigation, with the minimum possible teacher interference. This study allowed the subject functions; progressions and mathematical induction in a different way from that included in textbooks encourage students to have independent thinking, enabling the student to explore their potential, their skills and abilities such as logical and intuitive reasoning